Prophylactic alpha blockers fail to prevent postoperative urinary retention following orthopaedic procedures: evidence from a meta-analysis and trial sequential analysis of comparative studies - Shan, Lianliang; Sun, Ping; Zhang, Wenping; Zheng, Xuelian; Li, Hua; Wang, Songling (Frontiers in Pharmacology, 2023)
Objective The present systematic review and meta-analysis aimed to estimate the prophylactic effect of alpha blockers against postoperative urinary retention (POUR) in orthopaedic patients. Methods PubMed, Embase, Web of Science and Cochrane Library databases were searched between 1st January 1990 and March 1st 2023. The studies reporting the preventive efficacy of alpha blockers on POUR after orthopaedic procedures were identified. The pooled rates of POUR in the Intervention group (patients receiving alpha blockers) and the Control group (patients not receiving alpha blockers) were estimated and compared. The risk ratios (RRs) were calculated using the random-effects model. Subgroup analysis was performed based on surgical type. Trial sequential analysis (TSA) was conducted to confirm the robustness of pooled results. Results Seven studies containing 1607 patients were identified. The rates of POUR were similar between the two groups (Intervention group: 126/748 [16.8%] VS Control group: 168/859 [19.6%]; RR = 0.75; 95% confidence interval [CI] 0.51 to 1.09; P = 0.130; Heterogeneity: I2 = 67.1%; P = 0.006). No significant difference in the incidence of POUR was observed in either the Arthroplasty subgroup or Spine surgery subgroup. The result of TSA suggested that the total sample size of the existing evidence might be insufficient to draw conclusive results. Administrating alpha blockers was associated with a higher risk of complications (88/651 [13.5%] VS 56/766 [7.3%]; RR = 1.73; 95% CI 1.27 to 2.37; P = 0.0005; Heterogeneity: I2 = 0%; P = 0.69). Conclusion Prophylactic alpha blockers do not reduce the risk of POUR in orthopaedic procedures, and administrating these drugs was associated with a higher risk of complications.